Rancang Bangun Mesin Pengayak Pasir Semi Otomatis - Fudziyanto, Nurul; Satriya Hadi, Fajar; Arif Irfai, Mochamad; Anisa Rokhmahwati, Dian (Jurnal MOTION ( Manufaktur, Otomasi, Otomotif, dan Energi Terbarukan), 2022)
The sand sieving process is an activity that we often encounter in infrastructure development projects. But in the case of observations, problems are often encountered where workers still rely on simple or manual equipment. Based on the observations of the cases found, a semi-automatic sand sieving machine will be designed to help construction workers. In the process of making a sand sieve machine using a 9° sieve tilt angle with a sieve area of ​​3250 cm² and using a 0.5 cm x 0.5 cm mesh type. The driving source of the sand sieving machine uses an AC 0.5 HP electric motor with 1420 rpm. The eccentric shaft has a rotational speed of 115.36 rpm after receiving rotation from the AC motor. There are several tests on the sand sieving machine including tool functional testing, tool feasibility testing, and tool testing. In the functional test of the tool, testing all parts of the sand sieving machine obtained an average test value of 95%, in the feasibility test of the tool an average value of 100% was obtained, with a score of 4 and for testing the tool which included sand sieving, the average value has obtained the average of fine sand testing is 16.46 Kg and coarse sand is 3.53 Kg in 17.48 seconds, so it can be seen that the sand sieving machine can work optimally.